0
$\begingroup$

I have troubles solving this particular limit without using series expansion, L'Hospital rule or derivatives.

$$\lim_{x \to 0}{\frac{x\sin{x}+2(\cos{x}-1)}{x^3}}$$

I have tried multiplying by $(\cos{x}+1)$ and got rid of one $x$ in the denominator, but got arguably something even messier. I got this:

$$\lim_{x \to 0}{\frac{x(\cos{x}+1)-2\sin{x}}{x^2(\cos{x}+1)}}$$

Any help would be appreciated.

$\endgroup$
  • 1
    $\begingroup$ As $\cos x$ and $\sin x$ are defined as series I think you are asking for the impossible. $\endgroup$ – ancientmathematician Mar 25 at 16:12
  • 1
    $\begingroup$ Why do you need to do this without the most suitable tools for the task? $\endgroup$ – Clement C. Mar 25 at 16:35
  • $\begingroup$ To piggyback off of the comments above, any method that doesn't involve series will inevitably require a squeeze theorem argument that is more or less derived from series. $\endgroup$ – zugzug Mar 25 at 16:40
  • $\begingroup$ @ClementC.: for me this does give a thrill while tackling difficult problems using simpler tools. Occasionally one should enjoy such problems but not make them routine. $\endgroup$ – Paramanand Singh Mar 27 at 8:56
  • 1
    $\begingroup$ @ParamanandSingh Sometimes, the solution using simple tools is elegant. Sometimes, it just ends up long, technical, and contrived... $\endgroup$ – Clement C. Mar 27 at 11:13
2
$\begingroup$

Various limits are proved in this answer using basic tools only. In particular, we need $\lim_{t\to 0}\sin(t)/t=0$, $\lim_{t\to 0}(\cos(t)-1)/t=0$, and $\lim_{t\to 0}(t-\sin(t))/t^3=1/6$. $$\begin{align} \frac{x\sin x+2(\cos x-1)}{x^3}&=\frac{x(2\sin(x/2)\cos(x/2))+2(-2\sin^2(x/2))}{x^3} \\ &= \frac{\sin(x/2)}{x/2}\cdot\frac{x\cos(x/2)-2\sin(x/2)}{x^2} \end{align}$$ We have $\lim_{x\to 0}\sin(x/2)/(x/2)=1$. As for the second factor, $$\begin{align} \frac{x\cos(x/2)-2\sin(x/2)}{x^2} &= \frac{\left[x(\cos(x/2)-1)\right]+\left[\sin(x)-2\sin(x/2)\right]+\left[x-\sin(x)\right]}{x^2} \\ &= \frac{\cos(x/2)-1}{x}+\frac{2\sin(x/2)(\cos(x/2)-1)}{x^2}+\frac{x-\sin(x)}{x^2} \\ &= \frac 12\frac{\cos(x/2)-1}{x/2}+\frac 12\frac{\sin(x/2)}{x/2}\frac{\cos(x/2)-1}{x/2}+\frac{x-\sin(x)}{x^3}\cdot x \end{align}$$ You can finish with the aforementioned limits. The limit of the second factor is $0$. So the desired limit is $1\cdot 0=0$.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Brilliant, that's exactly what I was hoping for!! $\endgroup$ – Matthew Mar 25 at 17:40
2
$\begingroup$

I'll make use of some limits famously provable without the banned techniques:$$\begin{align}\frac{x\sin x+2(\cos x-1)}{x^3}&=\frac{2x\sin\frac{x}{2}\cos\frac{x}{2}-4\sin^2\frac{x}{2}}{x^3}\\&=\underbrace{\frac{4\sin^2\frac{x}{2}}{x^2}}_{\to1}\underbrace{\frac{\frac{x}{2}\cot\frac{x}{2}-1}{x}}_{\to0}.\end{align}$$The proof that $\lim_{x\to0}\frac{\sin x}{x}=\lim_{x\to0}\frac{\tan x}{x}=1$ is famous, whence$$\lim_{x\to0}\frac{x\cot x-1}{x}=\lim_{x\to0}\frac{x-\tan x}{x\tan x}=\lim_{x\to0}\frac{x-\tan x}{x^2}=0$$because $\lim_{x\to0}\frac{x-\tan x}{x^3}=-\frac13$ is famous too (see e.g. @bjorn93's link above).

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ One can prove that $(x-\tan x) /x^2\to 0$ using the famous inequality $\sin x <x<\tan x$ combined with Squeeze. $\endgroup$ – Paramanand Singh Mar 27 at 8:52
0
$\begingroup$

Whether series is allowed or not, here's the answer.

$x\sin x = x(x-x^3/3!+x^5/5!...)$ so the lowest order term is $x^2$. Simiilarly,

$2(1-\cos x)=2[1-(1-x^2/2!+x^4/4!...)]=2[x^2/2-x^4/4!...]$ so the lowest order term is $x^2$.

When you subtract the second from the first, the $x^2$ terms will cancel. The next lowest order in the numerator is $O(x^4)$. Then it is clear that the limit is $0$.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Note,

$$\frac{x\sin x + 2(\cos x -1)}{x^3} =\frac{\sin x}{x}\cdot \frac {x-2\tan\frac x2}{x^2}$$ and,

$$x-2\tan\frac x2 = O(x^3)$$

Thus,

$$\lim_{x \to 0}{\frac{x\sin{x}+2(\cos{x}-1)}{x^3}} = \lim_{x \to 0}\frac{\sin x}{x}\cdot \frac {O(x^3)}{x^2} =1\cdot 0=0$$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Let $ x\in\mathbb{R}^{*} $, observe that : $$ \fbox{$\begin{array}{rcl}\displaystyle\frac{x-\sin{x}}{x^{2}}=\frac{x}{2}\int_{0}^{1}{\left(1-t\right)^{2}\cos{\left(tx\right)}\,\mathrm{d}t}\end{array}$} $$

Using the fact that $ \left(\forall t\in\left[0,1\right]\right),\ \left|\cos{\left(tx\right)}\right|\leq 1 $, we have : \begin{aligned} \left|\frac{x-\sin{x}}{x^{2}}\right|=\frac{\left|x\right|}{2}\left|\int_{0}^{1}{\left(1-t\right)^{2}\cos{\left(tx\right)}\,\mathrm{d}t}\right|&\leq\frac{\left|x\right|}{2}\int_{0}^{1}{\left(1-t\right)^{2}\left|\cos{\left(tx\right)}\right|\mathrm{d}t}\\&\leq\frac{\left|x\right|}{2}\int_{0}^{1}{\left(1-t\right)^{2}\,\mathrm{d}t} \end{aligned}

Which means $ \left(\forall x\in\mathbb{R}^{*}\right),\ \left|\frac{x-\sin{x}}{x^{3}}\right|\leq\frac{\left|x\right|}{6} $, and thus $ \lim\limits_{x\to 0}{\frac{x-\sin{x}}{x^{2}}}=0 \cdot $

Let $ x\in\mathbb{R}^{*} $, observe that : $$ \fbox{$\begin{array}{rcl}\displaystyle\frac{x^{2}+2\left(\cos{x}-1\right)}{x^{3}}=\int_{0}^{1}{\left(1-t\right)^{2}\sin{\left(tx\right)}\,\mathrm{d}t}\end{array}$} $$

Using the fact that $ \left(\forall t\in\left[0,1\right]\right),\ \left|\sin{\left(tx\right)}\right|\leq t\left|x\right| $, we have : \begin{aligned} \left|\frac{x^{2}+2\left(\cos{x}-1\right)}{x^{3}}\right|=\left|\int_{0}^{1}{\left(1-t\right)^{2}\sin{\left(tx\right)}\,\mathrm{d}t}\right|&\leq\int_{0}^{1}{\left(1-t\right)^{2}\left|\sin{\left(tx\right)}\right|\mathrm{d}t}\\&\leq\left|x\right|\int_{0}^{1}{t\left(1-t\right)^{2}\,\mathrm{d}t} \end{aligned}

Which means $ \left(\forall x\in\mathbb{R}^{*}\right),\ \left|\frac{x^{2}+2\left(\cos{x}-1\right)}{x^{3}}\right|\leq\frac{\left|x\right|}{12} $, and thus $ \lim\limits_{x\to 0}{\frac{x^{2}+2\left(\cos{x}-1\right)}{x^{3}}}=0 \cdot $

Hence, $$ \lim_{x\to 0}{\frac{x\sin{x}+2\left(\cos{x}-1\right)}{x^{3}}}=\lim_{x\to 0}{\left(\frac{x^{2}+2\left(\cos{x}-1\right)}{x^{3}}-\frac{x-\sin{x}}{x^{2}}\right)}=0 $$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

As J.G. already shown it holds $$\begin{align}\frac{x\sin x+2(\cos x-1)}{x^3}&=\frac{2x\sin\frac{x}{2}\cos\frac{x}{2}-4\sin^2\frac{x}{2}}{x^3}\\&=\frac{4\sin^2\frac{x}{2}}{x^2}\frac{\frac{x}{2}\cot\frac{x}{2}-1}{x} \\ &= \left(\frac{\sin\frac{x}{2}}{\frac{x}{2}}\right)^2 \frac{f(x) - f(0)}{x - 0} \end{align}$$

for $f(x) = x\cot(x)$

So we get by the mean value theorem: $$\lim_{x\to 0} \frac{x\sin x+2(\cos x-1)}{x^3} = 0\cdot\lim_{x\to 0} f'(x) = 0\cdot1 = 0$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.